1988
DOI: 10.1164/ajrccm/137.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intrapulmonary Retention of Radiolabeled Neutrophils in Early Oxygen Toxicity

Abstract: Sequential lung injuries, such as oxygen toxicity followed by septicemia, are common during the adult respiratory distress syndrome (ARDS). As these forms of vascular injury may be mediated in part by polymorphonuclear leukocytes (PMN), aberrant interactions between PMN and previously injured pulmonary endothelium are of both theoretical interest and clinical importance. The present study was undertaken to test the hypothesis that early oxygen toxicity at a dose that injuries pulmonary endothelium relatively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…This was consistent with findings from other laboratories in which increases in the numbers of radiolabeled neutrophils were detected during hyperoxic lung injury (20). To determine if there was a temporal association between the appearance of neutrophils in the bronchoalveolar lavage fluid and the expression of mRNA for the adhesion molecules, ICAM-1, Eselectin, VCAM-1, or P-selectin, we exposed rats to an atmosphere of >95% oxygen for up to 72 hr.…”
Section: Rna Extaction and Northern Blot Analysissupporting
confidence: 87%
“…This was consistent with findings from other laboratories in which increases in the numbers of radiolabeled neutrophils were detected during hyperoxic lung injury (20). To determine if there was a temporal association between the appearance of neutrophils in the bronchoalveolar lavage fluid and the expression of mRNA for the adhesion molecules, ICAM-1, Eselectin, VCAM-1, or P-selectin, we exposed rats to an atmosphere of >95% oxygen for up to 72 hr.…”
Section: Rna Extaction and Northern Blot Analysissupporting
confidence: 87%
“…lung injury in hyperoxia [4,5], there is also data to suggest that hyperoxic lung injury may occur in the absence of neutrophils, as shown in a previous study, where neutrophil depletion by cyclophosphamide did not affect lung oedema in rats exposed to hyperoxia [23]. The production of free radicals has been shown to contribute significantly to hyperoxia-induced lung injury, and a number of studies have shown an improvement in survival with the use of free radical scavengers.…”
Section: Discussionmentioning
confidence: 89%
“…In adult rats, lung injury becomes evident after 50 h, and death usually occurs within 72 h of exposure to 100% oxygen [1]. Neutrophils accumulate in the lungs of rats soon after exposure to 100% oxygen, and may play a role in this form of acute lung injury [4,5].…”
mentioning
confidence: 99%
“…The migration of neutrophils into the lung, within the 1st week of the start of exposure to high oxygen, reflects an early response to oxidant stress (Rinaldo et al 1988). As exposure continues this diminishes, and PAMs (which also increase early) are found in increasing numbers (Horinouchi et al 1996).…”
Section: Discussionmentioning
confidence: 99%